DEVELOPMENT OF INTERACTIVE LEARNING MEDIA USING ARTICULATE STORYLINE 3 ON THE PLANE FIGURE MATERIALS - Novita Anggraini; Resyi A. Gani; Nurlinda Safitri (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
The development of interactive learning media using Articulate Storyline 3 on plane figure material aims to determine the development and feasibility of product development through interactive learning media. The research methodology used is Research and Development with the ADDIE approach (Analyze, Design, Development, Implementation, Evaluation) with the research subject of students at class IV-C SDN Julang Bogor. The instruments used in the research are media expert validation sheets, linguists and material experts with a total of three experts, students and teacher response instruments, and pre-test and post-test instruments. The validation results produce an average score of 93.7% with the